2013
DOI: 10.15288/jsad.2013.74.703
|View full text |Cite
|
Sign up to set email alerts
|

Causal Influence of Age at First Drink on Alcohol Involvement in Adulthood and Its Moderation by Familial Context

Abstract: ABSTRACT. Objective: Previous research has established a connection between early age at drinking initiation and greater alcohol involvement in adulthood, but it has not yet been established whether this is a causal effect. The current study used a multilevel discordant twin design to examine individual and contextual effects, and an interaction between these effects, of the age at drinking initiation on the frequency and quantity of drinking in adulthood. Method: Participants were 4,194 same-sex twins (2,264 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…Earlier twin pair analysis had suggested that the association between age at first drink and later development of alcohol dependence was non-causal and likely attributable largely to common genetic effects [9]. However, more recent studies using CTC have found that the relationship between earlier alcohol use and measures of adult alcohol involvement [18], adult alcohol dependence, and the use and abuse of other substances [19], may not be entirely attributable to familial factors shared between twins. Instead, they are likely to also be significantly, though less strongly, influenced by factors not shared by twins discordant for early alcohol use or age at first drink.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier twin pair analysis had suggested that the association between age at first drink and later development of alcohol dependence was non-causal and likely attributable largely to common genetic effects [9]. However, more recent studies using CTC have found that the relationship between earlier alcohol use and measures of adult alcohol involvement [18], adult alcohol dependence, and the use and abuse of other substances [19], may not be entirely attributable to familial factors shared between twins. Instead, they are likely to also be significantly, though less strongly, influenced by factors not shared by twins discordant for early alcohol use or age at first drink.…”
Section: Introductionmentioning
confidence: 99%
“…An important distinction is between causal and non-causal mechanisms. In a previous paper, we applied multilevel modeling of data from twin pairs to adjudicate between causal and non-causal mechanisms in explaining the inverse relation between the age of drinking initiation and the frequency and quantity of alcohol use in early adulthood (Deutsch et al, 2013). Effects at the individual level, family level, and their interaction explained the inverse relation between the age of alcohol use initiation and adult alcohol involvement.…”
mentioning
confidence: 99%
“…Future research may benefit from examining adolescent-specific environments relating to drinking behavior. Research indicates that early adolescent alcohol use is a possibly causal risk factor for higher adulthood alcohol (e.g., Deutsch et al, 2013; Deutsch et al, 2016). Extreme risk factors linked to high levels of alcohol use that exclusively occur in childhood and adolescence (e.g., child abuse, Dube et al, 2006; parental divorce, Sartor, Lynskey, Heath, Jacob & True, 2007), may account for environmental variance related to alcohol use.…”
Section: Discussionmentioning
confidence: 99%